Egg Cannibalism Varies With Sex, Reproductive Status, and Egg and Nymph Ages in Arma custos (Hemiptera: Asopinae) - Wu, Shaolong; Zeng, Weiai; Deng, Wan; Li, Mi; Hu, Wei; Cai, Hailin; Li, Youzhi; Xie, Pengfei; Tan, Lin; Zhou, Zhicheng (Frontiers in Ecology and Evolution, 2021)
Background: Egg cannibalism is common in nature. In China, Arma custos (Hemiptera: Asopinae) has been widely used as a natural enemy to control agricultural and forestry pests. A previous study showed that adult A. custos devour their eggs. However, no research has investigated the interaction between A. custos cannibalism and egg development. Clarifying the mechanisms involved in egg cannibalism by A. custos improves our understanding of the evolutionary relationships to enable more efficient mass rearing and biological control systems. Results: Virgin females showed a lower egg cannibalism inclination than gravid females. Both virgin and mated females showed a higher egg cannibalism inclination than virgin and mated males. The first and second instar nymphs did not devour eggs. The third, fourth, and fifth instar nymphs devoured eggs. Younger eggs were more readily eaten than older eggs. Neither A. custos nymphs nor female adults consumed all the available eggs, allowing an emergence ratio of >70%. Conclusion:Arma custos females exhibit a higher tendency for egg cannibalism than males. Egg cannibalism varies not only with the developmental stage of the eggs and nymphs but also with sex and reproductive status of A. custos females. These findings help us to better understand the evolutionary relationships in egg cannibalism by A. custos and contribute to the efficient mass rearing and realization of A. custos in biological control systems.